MODEL E-CUSTOMER LOYALTY PADA GENERASI Z PENGGUNA SHOPEEPAY - Syifa Pramudita Faddila; Hartelina Hartelina; Sonny Hersona (JURNAL LENTERA BISNIS, 2023)
Generation Z online shopping behavior trends tend to want convenience, practicality, and safety. The presence of a digital wallet introduces the public to a non-cash payment method that is practical, fast and profitable. In 2022 as many as 74% have used a digital wallet. This competition caused ShopeePay's position as a digital wallet provider to experience a decline with the presence of other digital wallets. The purpose of this research is to determine the effect of e-service quality on e-customer loyalty mediated by e-customer satisfaction variables in Generation Z who use ShopeePay. The population that the researchers determined were Buana Perjuangan Karawang University students in the Management study program class of 2019 to 2021 who were born in 1997-2012 (Generation Z) and 166 ShopeePay users, while the sample used was 117 students who were analyzed using the PLS SEM (Structural) method. Equation Model) with Partial Least Square basis. The results that the researchers got confirmed that e-service quality has an effect on e-customer loyalty through e-customer satisfaction, e-service quality has no direct effect on e-customer loyalty, e-customer satisfaction has an effect on e-customer loyalty, and e -service quality affects e-customer satisfaction.Â Key words: e-Customer Loyalty, e-Service Quality, e-Customer Satisfaction, Gen Z, ShopeePay